Brazil before and during COVID-19 pandemic: Impact on the practice and habits of physical exercise : Physical exercise during social isolation - Sonza, Anelise; da Cunha de Sá-Caputo, Danubia; Bachur, José Alexandre; Rodrigues de Araújo, Maria das Graças; Valadares Trippo, Karen Valadares Trippo; Ribeiro Nogueira da Gama, Dirceu Ribeiro Nogueira da Gama; Lago Borges, Daniel; Amaral Mendonça, Vanessa; Bernardo-Filho, Mario (Acta Biomedica Atenei Parmensis, 2020)
Introduction: The goal of this study was to investigate the practice and habits of physical exercise impact due to COVID-19 social isolation before and during the outbreak in Brazil and its mains macro-regions, which have social and economic disparities. Methods: This is an observational cross-sectional study through an online questionnaire survey. A self-administered survey (PEF-COVID19) was applied in the Brazilian general population, age ≥ 18 years. T-test for independent samples and Chi-square tests were used to compare Brazil and different macro-regions, p˂0.05. Results: 1,977 participants filled the survey and 1,845 were included; 80% of the included ones were in social isolation. In general, the self-related physical exercise practice before and during the COVID-19 pandemic and exercise characteristics were highly affected by the pandemic (p˂0.05). Sedentary behavior increased significantly (14.9 vs. 29.8%) and between the active ones, the frequency of PEx per week and duration of the PEx practice decreased significantly. The motivation to exercise also changed considering performance and health before and during the pandemic, respectively (10 vs. 5.6% and 72.4 vs. 79.1%). Also, the sample started to exercise less in the night and more in the afternoon, respectively (33.7 vs. 25.3% and 19.1 vs. 31.5%). Conclusions: The COVID-19 pandemic highly influenced the physical exercise practice and habits (frequency, duration, motivation, period to exercise) in Brazil and its main macro-regions. These results can be used to create measures, as home-based exercise programs, to avoid the harm of sedentary behaviors and mental health impact during and after the pandemic.